Alexithymia tendencies in adolescents Sidoharjo Gunungkidul - Purwaningsih, Indriyati Eko; Pratiwi, Diah Ayu (JURNAL SPIRITS, 2023)
This research was motivated by the increasing trend of Alexithymia among adolescents in Indonesia, including in some parts of the Gunung Kidul area. This research aimed to determine the level of Alexithymia tendency among groups of adolescents in Sidoharjo Village, Tepus District, based on gender. In addition, it also aimed to test empirically whether there is a difference in the tendency for Alexithymia in male and female adolescents. The hypothesis proposed in this research is that the tendency for Alexithymia in male adolescents in Sidoharjo Village is higher than in female adolescents. The sampling technique used in this research is proportional random sampling. The sample size was determined using the Slovin formula. Alexithymia scale was used as the measuring tool, prepared based on Nemiah's theory. The reliability of the measurement results obtained was 0.819. The results of this study show that the majority of Alexithymia tendencies in adolescents are in the moderate category, but 20.12% are in the high category, and 4.14% are in the very high category. Male adolescents have a higher tendency for Alexithymia (mean: 52.95) than female adolescents (mean: 47.25).